Treatment of advanced heart failure in a young man with familial cardiomyopathy. - Massin, E K (1998)
We report the case of a young man with familial cardiomyopathy whose symptoms became difficult to control as his myopathy worsened. He had persistent cardiac arrhythmias and was intolerant of angiotensin-converting enzyme inhibitor therapy. His case illustrates the difficulties that can be encountered in treating patients with advanced heart failure.